2016
DOI: 10.1098/rsif.2016.0734
|View full text |Cite
|
Sign up to set email alerts
|

Synchronization and collective swimming patterns in fish (Hemigrammus bleheri)

Abstract: In this work, we address the case of red nose tetra fish Hemigrammus bleheri swimming in groups in a uniform flow, giving special attention to the basic interactions and cooperative swimming of a single pair of fish. We first bring evidence of synchronization of the two fish, where the swimming modes are dominated by 'out-phase' and 'in-phase' configurations. We show that the transition to this synchronization state is correlated with the swimming speed (i.e. the flow rate), and thus with the magnitude of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

13
116
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 83 publications
(131 citation statements)
references
References 30 publications
13
116
0
2
Order By: Relevance
“…1, Left. This characteristic pattern has already been identified in a previous study on H. bleheri fish triplets (16). As can be observed, this reduced set of geometric parameters determines the most basic school, consisting of a fish triplet, and we use it here to describe the spatial pattern for larger groups of individuals.…”
Section: Resultsmentioning
confidence: 75%
See 3 more Smart Citations
“…1, Left. This characteristic pattern has already been identified in a previous study on H. bleheri fish triplets (16). As can be observed, this reduced set of geometric parameters determines the most basic school, consisting of a fish triplet, and we use it here to describe the spatial pattern for larger groups of individuals.…”
Section: Resultsmentioning
confidence: 75%
“…The phase difference is calculated by a peak identification routine on each time series of the tail-beating amplitude. The synchronization effect for H. bleheri was already pointed out in a study with fish pairs (16), in which observations of a large set of experiments showed that >90% of the fish pairs studied were synchronized when swimming at high speed. Fig.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…Herskin and Steffensen [11] 24 measured both tail beat frequency and oxygen consumption in sea bass Dicentrarchus 25 labrax, and also found strong evidence for energy saving. Johansen et al [12] estimated 26 that trailing fish in a school (striped surfperch Embiotoca lateralis) benefited from over 27 25% reduction in oxygen consumption, based on correlations between swimming speeds, 28 pectoral fin beat frequency, and oxygen consumption of solitary fish. Marras et al [13] 29 also inferred reduced costs of swimming from measurements of tail-beat frequency of 30 grey mullet Liza aurata alone and in schools, combined with relationships between 31 tail-beat frequency and activity metabolism.…”
mentioning
confidence: 99%